2007
DOI: 10.1111/j.1528-1167.2007.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Epilepsies with Seizures Precipitated by Fever and SCN1A Abnormalities

Abstract: Summary:Purpose: SCN1A is the most clinically relevant epilepsy gene, most mutations lead to severe myoclonic epilepsy of infancy (SMEI) and generalized epilepsy with febrile seizures plus (GEFS+). We studied 132 patients with epilepsy syndromes with seizures precipitated by fever, and performed phenotypegenotype correlations with SCN1A alterations.Methods: We included patients with SMEI including borderline SMEI (SMEB), GEFS+, febrile seizures (FS), or other seizure types precipitated by fever. We performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
128
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 27 publications
10
128
0
1
Order By: Relevance
“…At least 80% of cases are associated with heterozygous loss-of-function mutations in the exons of SCN1A, which encodes the brain type-I voltage-gated sodium channel Na V 1.1 (5). DS begins in the first year of life, with fever-or temperature-sensitive seizures that often evolve into refractory generalized tonic-clonic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…At least 80% of cases are associated with heterozygous loss-of-function mutations in the exons of SCN1A, which encodes the brain type-I voltage-gated sodium channel Na V 1.1 (5). DS begins in the first year of life, with fever-or temperature-sensitive seizures that often evolve into refractory generalized tonic-clonic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…4,15 In addition, linkage studies have identified 7 genomic regions likely to harbor genes increasing risk for GEFSϩ and 5 regions likely to harbor genes increasing risk for FS (table 1). [16][17][18][19][20][21][22][23][24][25][26] Two loci originally described as FS loci (FEB3 and FEB4) were reported in pedigrees best classified as GEFSϩ due to phenotypes beyond typical FS.…”
mentioning
confidence: 99%
“…When considering only clinically diagnosed DS cases, combination of sequencing and MLPA testing approach showed a 85.7% sensitivity of causative DNA sequence variant detection, even higher than was reported in previous studies: 82.7% (Ohmori et al 2002), 71% (Marini et al 2007), 73% (Depienne et al 2009). The higher sensitivity observed in present study could be the result of very strict criteria during clinical diagnosis.…”
Section: Discussionmentioning
confidence: 51%
“…These can be, however, presumed with a relatively high probability as it is generally accepted that haploinsufficiency or gain of toxic function of truncated proteins may play a crucial role in the pathogenesis of the disease. Loss-of-function SCN1A sequence variants, such as nonsense and frameshift causing ones, were reported to be the predominant genetic abnormalities seen in DS patients and are usually associated with the most severe phenotypes and reproductive disadvantage (Sugawara et al 2001;Marini et al 2007). Most of the already described truncating variants, similarly to those identified by us, are found in the 5´ end of the SCN1A gene while the proteins altered in such way likely undergoes a nonsensemediated decay (NMD) pathway (Holbrook et al 2004).…”
Section: Discussionmentioning
confidence: 99%